2020
DOI: 10.1016/j.dci.2019.103485
|View full text |Cite
|
Sign up to set email alerts
|

The immunobiological interplay between Pseudosuccinea columella resistant/susceptible snails with Fasciola hepatica: Hemocytes in the spotlight

Abstract: The Fasciola hepatica/Pseudosuccinea columella interaction in Cuba involves a unique pattern of phenotypes; while most snails are susceptible, some field populations are naturally resistant to infection and parasites are encapsulated by snail hemocytes. Thus, we investigated the hemocytes of resistant (R) and susceptible (S) P. columella, in particular morphology, abundance, proliferation and in vitro encapsulation activity following exposure to F. hepatica. Compared to susceptible P. columella, hemocytes from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 79 publications
0
15
0
Order By: Relevance
“…In this sense, histological sections of exposed resistant P. columella showed that the penetration of F. hepatica miracidium into the snail is rapidly followed by an effective encapsulation of the parasite larvae by the hemocytes of the host (circulating immune cells of snails), observed at 24 h post-exposure ( 28 ). This powerful immunological reaction is believed to be at the base of the resistance of P. columella to F. hepatica ( 17 , 28 ).…”
Section: Resistance Of P Columella To F Hepatica In Cuba: What We Knowmentioning
confidence: 99%
See 3 more Smart Citations
“…In this sense, histological sections of exposed resistant P. columella showed that the penetration of F. hepatica miracidium into the snail is rapidly followed by an effective encapsulation of the parasite larvae by the hemocytes of the host (circulating immune cells of snails), observed at 24 h post-exposure ( 28 ). This powerful immunological reaction is believed to be at the base of the resistance of P. columella to F. hepatica ( 17 , 28 ).…”
Section: Resistance Of P Columella To F Hepatica In Cuba: What We Knowmentioning
confidence: 99%
“…Although these attempts aimed at increasing the probability of encounter of compatible genotypic host–parasite individual combinations and at potentially decreasing the effectivity of the immune response of the host (such effects have been observed in susceptible populations used as control), they have all failed in rendering phenotypically resistant snails infected. Such stability and universality (at least at the above mentioned scale) of this phenotype paired to the potent immune response associated to it ( 17 , 28 ), point at the occurrence of an immunological resistance that is not restricted by specific interactions of matching genotypes between the host and the parasite. It is, therefore, rather a phenomenon of immunological resistance than one of incompatibility and that, noteworthy, has been selected in nature ( 18 , 28 ).…”
Section: Resistance Of P Columella To F Hepatica In Cuba: What We Knowmentioning
confidence: 99%
See 2 more Smart Citations
“…On the intermediate host side, a few hours following infection, there is no significant haemocyte (snail immune cells) proliferation. In addition, lower expression of the proliferative cytokine granulin and lower levels of in vitro encapsulation activity (=protective immune response towards Fasciola ) of haemocytes against F. hepatica larvae have been found in susceptible over resistant Pseudosuccinea columella snails (Alba et al ., 2020).…”
Section: Biological Factors: a Glance At Highly Evolved And Adaptablementioning
confidence: 99%